Exposure to an environmentally relevant concentration of chlorpyrifos induces transcriptional changes and neurotoxicity in Poecilia gillii without clear behavioral effects - Daniel Sánchez-González; Kinndle Blanco-Peña; Frank Solano-Campos; Karla Solano; Freylan Mena (Ecotoxicology and Environmental Safety)
Overusing chlorpyrifos (CPF) in tropical countries such as Costa Rica poses a potential risk to freshwater ecosystems. This study investigated the effects of transient exposure to an environmentally relevant CPF concentration on the native fish species Poecilia gillii, employing a comprehensive approach that evaluated multiple levels of biological organization. Using RT-qPCR, we quantified transcript changes in genes involved in various biological processes, including inflammation and apoptosis; annexin A1 (anxa1b), cytokine regulation; cytokine-inducible SH2-containing protein (cish), redox reactions; NADH oxidoreductase subunit A2 (ndufa2), protein translocation; Sec61 gamma subunit (sec61g), and biotransformation; glutathione S-transferase rho (gstr). Additionally, we measured biochemical biomarkers such as phase I; 7-ethoxyresorufin-O-deethylase (EROD) and phase II; glutathione S-transferase (GST) biotransformation enzymes, oxidative stress markers; catalase (CAT) and lipid peroxidation (LPO), and conducted behavioral tests to assess swimming fitness and antipredator reactions. Neurotoxicity was assessed by measuring brain and muscle tissue cholinesterase (ChE) activity. Following 48 h of exposure to 5.5 µg/L CPF, we observed significant downregulation of the sec61g and gstr genes, decreased CAT activity, and neurotoxic effects, as indicated by reduced ChE activity in muscle. Although no significant behavioral changes were detected, our results suggest that short-term exposure to environmentally relevant CPF concentrations can disrupt gene expression, compromising biotransformation and protein synthesis in P. gillii juveniles. Moreover, the observed neurotoxicity, which is consistent with the mechanism of action of CPF, may lead to subtle behavioral changes. This study provides evidence of the sublethal effects of CPF on nontarget organisms, highlighting the importance of considering gene expression changes when assessing CPF toxicity.